Effects of crystal phase and composition on structurally ordered Pt–Co–Ni/C ternary intermetallic electrocatalysts for the formic acid oxidation reaction. Issue 14 (16th March 2018) - Chen, Lingxuan; Zhu, Jing; Xuan, Cuijuan; Xiao, Weiping; Xia, Kedong; Xia, Weiwei; Lai, Chenglong; Xin, Huolin L.; Wang, Deli
Abstract : An ordered structure and multiple components in combination promote enhanced activity and stability of Pt-based catalysts toward the FAOR. Abstract : To enhance the electrocatalytic performance of the formic acid oxidation reaction (FAOR), structurally ordered face-centered tetragonal (fct) Pt–Co–Ni/C intermetallic nanoparticles were synthesized via an impregnation reduction method, followed by post heat-treatment. It was found that an ordered intermetallic PtCo phase prevails rather than PtNi as the principal part for the ternary Pt–Co–Ni alloy after being annealed at high temperature, namely, Ni atoms merely serve as the substitute for Co in the lattice of Pt–Co–Ni intermetallics possessing the same atomic stack as PtCo intermetallics. In addition, there is a limitation for Ni to replace Co for the intermetallic PtCo phase, otherwise, most likely excessive Ni would replace the Pt atoms and damage the atomically ordered structure. Benefiting from the ordered structural features and rational introduction of the third transition metal to modify the distance between Pt and Pt atoms, the Pt–Co–Ni/C ordered intermetallic nanoparticles exhibit an enhancement in catalytic activity for the FAOR compared with Pt/C, the PtNi/C alloy and ordered intermetallic PtCo/C nanoparticles. Furthermore, the presence of Ni in the ordered intermetallic Pt–Co–Ni/C catalyst leads to a noticeable improvement in durability compared with the ordered intermetallic PtCo/C catalyst. The present work reveals opportunities for the rational design of ternary electrocatalysts with enhanced catalytic performance for fuel cell applications.